Ilex paraguariensis Extracts: A Source of Bioelements and Biologically Active Compounds for Food Supplements - Elżbieta Rząsa-Duran; Bożena Muszyńska; Agnieszka Szewczyk; Katarzyna Kała; Katarzyna Sułkowska-Ziaja; Joanna Piotrowska; Włodzimierz Opoka; Agata Kryczyk-Poprawa (Applied Sciences, 2024)
Ilex paraguariensis, commonly known as yerba mate, is a plant belonging to the holly genus Ilex and the Aquifoliaceae family, indigenous to South America, and is used for the production of yerba mate. Yerba mate is renowned for its abundance of essential nutrients and bioactive compounds. Based on test results, it can be assumed that the selection of raw material for the preparation of extracts as well as the extraction method significantly influence the final content of biologically active compounds in the extracts. Consequently, this variability impacts the ultimate concentration of biologically active substances within the end product, potentially influencing human consumption. The present study aimed to quantify and compare the content of selected biological active compounds in supplements and products containing I. paraguariensis extracts, along with organic yerba mate dried through a smoke-free process, available in the European market (P-1–P-10). The evaluation focused on antioxidant substances such as neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 4-feruloylquinic acid, isochlorogenic acid, rutoside astragalin, and caffeine. Additionally, the concentration of specific macro and trace elements was ascertained. The antioxidant compound makeup differs between methanol-extracted samples and aqueous extracts. In both cases, methanol extracts, particularly those in instant and traditional herb forms, showed the highest content of organic compounds with antioxidant properties (such as phenolic compounds and caffeine). The highest content of chlorogenic acid was detected in both methanol (14.7412 mg/g d.w.) and water (8.3120 mg/g d.w.) extracts in product P-4. The caffeic acid content ranged from 0.1491 mg/g d.w. to 1.7938 mg/g d.w. in methanol extracts and from 0.0760 mg/g d.w. to 0.4892 mg/g d.w. in water extracts. The neochlorogenic acid content ranged from 2.6869 to 23.9750 mg/g d.w. in ethanol extracts and from 0.4529 to 10.2299 mg/g d.w. in water extracts. Therefore, the traditional preparation of yerba mate as a water infusion does not fully exploit the raw material’s potential. Among the tested products, only the dietary supplement in capsule form contained protocatechuic acid, which was not present in any other tested products. Conversely, compounds characteristic of yerba mate found in other preparations were absent in this supplement. The caffeine content was also the lowest in this product. The determined content of active substances did not consistently match the declarations made by producers if stated on the packaging.